1990
DOI: 10.1063/1.102584
|View full text |Cite
|
Sign up to set email alerts
|

Influence of barrier inhomogeneities on noise at Schottky contacts

Abstract: Electronic properties of Schottky diodes depend sensitively on spatial inhomogeneities of the metal/semiconductor interface. We find that, contrary to previous theories for low-frequency noise, the electronic properties of Schottky contacts cannot be understood if one neglects spatial fluctuations of the Schottky barrier height. Our systematic investigation of several silicide/silicon diodes yields as an empirical law that excess noise increases drastically when the standard deviation σs of the spatial distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 7 publications
5
50
0
Order By: Relevance
“…The noise behavior observed in BH-QCLs at room temperature in this study and as a function of temperature in our former work [12] shows similar features as reported by Güttler et al [31] for Schottky diodes. At low temperature, they showed that the electrical noise of the diodes increased upon cooling, while at room temperature an increase in the noise with the injected current was observed.…”
Section: A Potential Additional Noise Source In Bh-qclssupporting
confidence: 77%
See 1 more Smart Citation
“…The noise behavior observed in BH-QCLs at room temperature in this study and as a function of temperature in our former work [12] shows similar features as reported by Güttler et al [31] for Schottky diodes. At low temperature, they showed that the electrical noise of the diodes increased upon cooling, while at room temperature an increase in the noise with the injected current was observed.…”
Section: A Potential Additional Noise Source In Bh-qclssupporting
confidence: 77%
“…At low temperature, they showed that the electrical noise of the diodes increased upon cooling, while at room temperature an increase in the noise with the injected current was observed. Explaining their observations, Güttler et al [31] have shown a cor-relation between the magnitude of the observed noise and the strength of spatial inhomogeneities at the metal-semi-conductor interface in Schottky diodes. An analogy can be made between the described structure and the BH laser configuration, where not only a highly doped cladding act-ing somehow like a metal is deposited onto an insulator, but periodically doped layers are also in contact with the lat-eral insulator.…”
Section: A Potential Additional Noise Source In Bh-qclsmentioning
confidence: 99%
“…The Gaussian distribution function was used to obtain fits to the histograms. The probability of SBH, P (Φ B ), has the form [45,46]:…”
Section: Resultsmentioning
confidence: 99%
“…The current variation at grain boundary is attributed to the change in the energy band diagram at the interface between two grains of this p-type polycrystalline semiconductor, analogously to what found in literature. [62,63] According to the interpretation provided by this literature results, the electrically charged grain boundaries act as hole traps. The current is affected by the capture and emission of holes by the interface states and its modulation derives from a fluctuation of the potential barrier height.…”
Section: Discussionmentioning
confidence: 99%